Analisis Sistem Pengelolaan Ruang Laktasi Di Perusahaan Swasta Wilayah Dinas Kesehatan Kabupaten Semarang (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: The efforts to improve the coverage of exclusive breastfeeding had long done but the success of theprogram coverage was low. Exclusive breastfeeding coverage area of DKK Semarang District in 2011 of 20% wasstill below the target of 80%. In 2012 had published Government Regulation (PP) number 33 on Exclusive Breastfeeding followed by the publication of the Regulation of the Minister of Health that regulates donor breast milk,providing space Lactation in workplaces, public facilities, procedures for the use of infant formula and procedure forthe imposition of administrative sanctions for health workers and providers of health care facilities. The sanctionswere given gradually from verbal warning, written, until licence revocation.4Objective: This study aimed to analyze the management system lactation room in a private company in terms ofaspects of input, process and output working area of Semarang Health Official.Method: This type of research was qualitative descriptive exploratory presented through in-depth interviews. Theselection informant by purposive, collecting data through interviews (depth interview) in the key informants was 5 incharge of space lactation in private companies, and the informant triangulation was 5 Human Resource Division inprivate company, 5 employees of work breastfeeding, 1 person worked in Health Official Semarang. The data werecollected by in-depth interview technique. The data analysis using content analysis method (content analysis).Result: The results of the input variables, about human resources, already met the minimum requirement that wasthe latest education was Bachelor of Medicine and Diploma of Nursing and Midwifery. The main funding sourcewas pure of each private company. The infrastructure facilities were provided purely from private company. In theprocess discovered that not all space lactation creates an annual plan.Conclusion: Organizing space lactation private companies, not all have a clear organizational structure. The implementation of lactation space yet everything goes well. The evaluation and supervision had been carried out on aregular basis from the relevant authorities. The activities in integration room had not all goes well lactation.Keywords: Lactation Space, Input, Process and Output